Metastatic melanoma - Cumpa-Quiroz, Robert (2021)
A 69-year-old male patient with hyperpigmented lesion in the right foots ole, nausea and vomitis, weight loss, adenomegaly in the inguinal and cervical regions and proptosis of the right eye. The images revealed metastasis in the thoracic lymph nodes, brain and right orbital region. Histopathological study offoot lesion and duodenal mucosa confirmed the presence of melanoma.